Pengaruh Good Governance, Reformasi Administrasi Perpajakan Dan Sanksi Administrasi Pajak Terhadap Kepatuhan Wajib Pajak Restoran Pada Wilayah Administrasi Kecamatan Cempaka Putih Jakarta Pusat - Yayak Heriyanto; Nila Sari (Jurnal Pajak Vokasi (JUPASI), 2021)
This study conducted to analys the effect of good governance, tax administration reform, and tax administration sanctions toward the compliance of restaurant taxpayers in the Cempaka Putih sub-district, Central Jakarta. This research is motivated by the cases of restaurant tax disobedience based on sub-district UPPRD database related to restaurant taxpayers, means restaurant management in Cempaka Putih sub-district, Central Jakarta. This study uses a quantitative approach in analyzing primary data with statistics analyses system of IBM SPSS Statistics 25. The total population in this researche are 394 restaurants based on UPPRD database, wich sample used in this study is 78 restaurant or 25% from total population referring to Soeharsimi Arikunto's sampling technique by random sampling approach for collecting primary data. The analysis results show that simultaneously Good Governance, Tax Administration Reform, and Tax Administration Sanctions have an effect of 54.1% toward restaurant taxtpayer compliance, while the remaining 45.9% is influenced by other variables.